Measuring acute postoperative pain using the visual analog scale: the minimal clinically important difference and patient acceptable symptom state. (March 2017) - Myles, P.S.; Myles, D.B.; Galagher, W; Boyd, D; Chew, C; MacDonald, N; Dennis, A
Abstract: Background: The 100 mm visual analog scale (VAS) score is widely used to measure pain intensity after surgery. Despite this widespread use, it is unclear what constitutes the minimal clinically important difference (MCID); that is, what minimal change in score would indicate a meaningful change in a patient's pain status. Methods: We enrolled a sequential, unselected cohort of patients recovering from surgery and used a VAS to quantify pain intensity. We compared changes in the VAS with a global rating-of-change questionnaire using an anchor-based method and three distribution-based methods (0.3 sd, standard error of the measurement, and 5% range). We then averaged the change estimates to determine the MCID for the pain VAS. The patient acceptable symptom state (PASS) was defined as the 25th centile of the VAS corresponding to a positive patient response to having made a good recovery from surgery. Results: We enrolled 224 patients at the first postoperative visit, and 219 of these were available for a second interview. The VAS scores improved significantly between the first two interviews. Triangulation of distribution and anchor-based methods resulted in an MCID of 9.9 for the pain VAS, and a PASS of 33. Conclusions: Analgesic interventions that provide a change of 10 for the 100 mm pain VAS signify a clinically important improvement or deterioration, and a VAS of 33 or less signifies acceptable pain control (i.e. a responder), after surgery.